Host Susceptibility to the Attaching and Effacing Bacterial Pathogen Citrobacter rodentium - Vallance, Bruce A. (American Society for Microbiology, 2003)
Many studies have shown that genetic susceptibility plays a key role in determining whether bacterial pathogens successfully infect and cause disease in potential hosts. Surprisingly, whether host genetics influence the pathogenesis of attaching and effacing (A/E) bacteria such as enteropathogenic and enterohemorrhagic Escherichia coli has not been examined. To address this issue, we infected various mouse strains with Citrobacter rodentium, a member of the A/E pathogen family. Of the strains tested, the lipopolysaccharide (LPS) nonresponder C3H/HeJ mouse strain experienced more rapid and extensive bacterial colonization than did other strains. Moreover, the high bacterial load in these mice was associated with accelerated crypt hyperplasia, mucosal ulceration, and bleeding, together with very high mortality rates. Interestingly, the basis for the increased susceptibility was not due to LPS hyporesponsiveness, as the genetically related but LPS-responsive C3H/HeOuJ and C3H/HeN mouse strains were also susceptible to infection. Analysis of the intestinal pathology in these susceptible strains revealed significant crypt epithelial cell apoptosis (terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end label staining) as well as bacterial translocation to the mesenteric lymph nodes. Further studies with infection of SCID (T- and B-lymphocyte-deficient) C3H/HeJ mice demonstrated that loss of lymphocytes had no effect on bacterial numbers but did reduce crypt cell apoptosis and delayed mortality. These studies thus identify the adaptive immune system, crypt cell apoptosis, and bacterial translocation but not LPS responsiveness as contributing to the tissue pathology and mortality seen during C. rodentium infection of highly susceptible mouse strains. Determining the basis for these strains' susceptibility to intestinal colonization by an A/E pathogen will be the focus of future studies.